TWO NEW ALGEBRAIC INEQUALITIES WITH 2n VARIABLES XIAO-GUANG CHU CHENG-EN ZHANG Suzhou Hengtian Trading Co. Ltd. Eastern Baodai Road, Suzhou City, Jiangsu Province, 215128, China EMail: srr345@163.com Department of Information Engineering, Xuchang Vocational Technical College 1060 Xuchang City, Henan Province, 461000, China EMail: zhangchengen63@163.com Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi vol. 8, iss. 4, art. 102, 2007 Title Page FENG QI Research Institute of Mathematical Inequality Theory, Henan Polytechnic University, Jiaozuo City, Henan Province, 454010, China. EMail: qifeng618@gmail.com Received: 12 March, 2007 Accepted: 05 December, 2007 Communicated by: D. Hinton 2000 AMS Sub. Class.: 26D05; 26D07; 26D15. Key words: Algebraic inequality, Cauchy’s inequality, Combinatorial identity, Algebraic identity. Abstract: In this paper, by proving a combinatorial identity and an algebraic identity and by using Cauchy’s inequality, two new algebraic inequalities involving 2n positive variables are established. Acknowledgements: The authors would like to express heartily their thanks to the anonymous referees for their valuable corrections and comments on the original version of this paper. Contents JJ II J I Page 1 of 13 Go Back Full Screen Close Contents 1 Main results 3 2 Two Lemmas 4 3 Proofs of the Main Results 7 Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi vol. 8, iss. 4, art. 102, 2007 Title Page Contents JJ II J I Page 2 of 13 Go Back Full Screen Close 1. Main results When solving Question CIQ-103 in [2] and Question CIQ-142 in [5], the following two algebraic inequalities involving 2n variables were posed. Theorem 1.1. Let n ≥ 2 and xi for 1 ≤ i ≤ 2n be positive real numbers. Then (1.1) 2n X x2n−1 n i ≥ 2n−2 . 2n−1 2 (2n − 1) k6=i (xi + xk ) P2n i=1 Equality in (1.1) holds if and only if xi = xj for all 1 ≤ i, j ≤ 2n. Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi vol. 8, iss. 4, art. 102, 2007 Theorem 1.2. Let n ≥ 2 and yi for 1 ≤ i ≤ 2n be positive real numbers. Then (1.2) 2n X i=1 yi−1|2n yi2 Pi+n−2 k=i yk|2n ≥ 2n , n−1 where m|2n means m mod 2n for all nonnegative integers m. Equality in (1.2) holds if and only if yi = yj for all 1 ≤ i, j ≤ 2n. Pi+n−2 The notation k=i yk|2n in Theorem 1.2 could be illustrated with an example P to clarify the meaning: If n = 5 then 12 k=9 yk|10 = y9 + y10 + y1 + y2 . In this article, by proving a combinatorial identity and an algebraic identity and by using Cauchy’s inequality, these two algebraic inequalities (1.1) and (1.2) involving 2n positive variables are proved. Moreover, as a by-product of Theorem 1.1, the following inequality is deduced. Theorem 1.3. For n ≥ 2 and 1 ≤ k ≤ n − 1, k X 2n 22(n−1) k(k + 1) (1.3) < p(p + 1) . k−p n p=1 Title Page Contents JJ II J I Page 3 of 13 Go Back Full Screen Close 2. Two Lemmas In order to prove inequalities (1.1) and (1.2), the following two lemmas are necessary. Lemma 2.1. Let n and k be natural numbers such that n > k. Then n−1 X 2 2n (n − k) (2.1) = 4n−1 n. k k=0 Proof. It is well known that n n n−1 n = , k =n , k n−k k k−1 X 2n n n−2 2n k(k − 1) = n(n − 1) , = 4n . k k−2 i i=0 Then n−1 X 2n (n − k) k k=0 X n−1 n−1 n−1 X X 2n 2n 2n 2 =n − (2n − 1) k + k(k − 1) k k k k=0 k=0 k=0 n−1 n−1 n−1 X X X 2n 2n − 1 2n − 2 2 − 2n(2n − 1) + 2n(2n − 1) =n k k−1 k−2 k=0 k=1 k=2 2 Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi vol. 8, iss. 4, art. 102, 2007 Title Page Contents JJ II J I Page 4 of 13 Go Back Full Screen Close =n 2 n−1 X 2n k=0 4n − = n2 2 = 4n−1 n + k 2n n − 2n(2n − 1) n−2 X 2n − 1 k=0 2n−1 2 − 2n(2n − 1) 4n(2n − 1) 2n−1 − n2 n k −2 2 2n n + 2n(2n − 1) n−3 X 2n − 2 k=0 n−1 2n−1 4 n−1 + 2n(2n − 1) − 2n(2n − 1) 2n−2 +2 n−1 2 k − 2n−2 n−1 2n−2 n−2 −2 2n−2 n−2 2 2n − 2 2 = 4 n + 2(2n − 1) − n(2n − 1) − n(2n − 1) − 2(2n − 1)(n − 1) n−1 n−1 = 4 n. n−1 Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi vol. 8, iss. 4, art. 102, 2007 The proof of Lemma 2.1 is complete. Title Page Lemma 2.2. Let n ≥ 2 and yi for 1 ≤ i ≤ 2n be positive numbers. Denote xi = yi + yn+i for 1 ≤ i ≤ n and Contents (2.2) An = 2n X i=1 yi n−1+i X yk|2n , k=i+1 where m|2n means m mod 2n for all nonnegative integers m. Then X (2.3) An = xi xj . 1≤i<j≤n Proof. Formula (2.2) can be written as (2.4) An = y1 (y2 + · · · + yn ) + y2 (y3 + · · · + yn+1 ) + · · · + y2n (y1 + · · · + yn−1 ). JJ II J I Page 5 of 13 Go Back Full Screen Close From this, it is obtained readily that X An = yi yj − 1≤i<j≤n X xi xj = yi yn+i i=1 1≤i<j≤2n by induction on n. Since X n X Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi (yi + yi+n )(yj + yj+n ), 1≤i<j≤n vol. 8, iss. 4, art. 102, 2007 then An = X 1≤i<j≤2n yi yj − n X i=1 yi yi+n = X (yi + yi+n )(yj + yj+n ) = 1≤i<j≤n X xi xj , Title Page 1≤i<j≤n which means that identity (2.3) holds. The proof of Lemma 2.2 is complete. Contents JJ II J I Page 6 of 13 Go Back Full Screen Close 3. Proofs of the Main Results Proof of Theorem 1.1. By Cauchy’s inequality [1, 4], it follows that (3.1) 2n X i=1 2n X 2n X x2n−1 i xi (xi + xj )2n−1 ≥ P2n 2n−1 k6=i (xi + xk ) i=1 j6=i 2n X !2 xni . i=1 Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi Consequently, it suffices to show !2 2n 2n X 2n X X n−1 n (2n − 1)4 xi ≥n xi (xi + xj )2n−1 i=1 vol. 8, iss. 4, art. 102, 2007 i=1 j6=i n−1 ⇐⇒ (2n − 1)4 2n X Title Page x2n i 2n−1 + (2n − 1)2 i=1 ≥n 2n−2 ⇐⇒ (2n − 1) 2 xni xnj Contents 1≤i<j≤2n n X 2n − 1 k=0 X k −n 2n X 2n − 1 + 2n − k X 2n X 2n xi2n−k xkj JJ II J I i=1 j6=i Page 7 of 13 x2n i Go Back i=1 X 2n − 1 2n−1 + (2n − 1)2 − 2n xni xnj n 1≤i<j≤2n 2n 2n n−1 X 2n − 1 2n − 1 X X 2n−k k xi xj . ≥n + k 2n − k i=1 j6=i k=1 Full Screen Close Since n k (3.2) X 2n 2n−1 (2n − 1)2 −n xni xnj n 1≤i<j≤2n n n−k = n k and = 2n−2 + (2n − 1) 2 n−1 k −n n−1 k−1 + 2n X x2n i , the above inequality becomes −n i=1 Utilization of 2n−2 2 2 P2n k=0 2n k = 22n and − n + (2n − 1)2 2n−1 2n 0 2n 2n n−1 X 2n X X k=1 = 2n 2n k xi2n−k xkj ≥ 0. i=1 j6=i = 1 yields Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi vol. 8, iss. 4, art. 102, 2007 2n−1 X 2n 2n −n −n n k k=1,k6=n " 2n # X 2n = 22n n − 2n − n − 2 = 0. k k=0 Substituting this into (3.2) gives ) ( n−1 " # 2n−2q−2 q 2n X X X X 2n (3.3) 22n−2 − n − n xqi xqj x2n−2q−k−2 xkj i k q=0 k=0 i=1,j=1,i6=j k=1 Title Page Contents JJ II J I Page 8 of 13 Go Back Full Screen 2 × (xi − xj ) ≥ 0, where Pq k=1 2n k = 0 for q = 0. Employing (2.1) in the above inequality leads to " # p n−1 X X 2n (2n − 2p − 1) 22n−2 − n k p=0 k=0 Close = 22n−2 n2 − n ( n−1 X (2n − 2p − 1) p=0 2n−2 2 n −n =2 n−1 X p X 2n k=0 2 (n − k) k=0 2n k ) k = 0. This implies that inequality (3.3) is equivalent to ( n " # 2n k−1 X X X 2n (3.4) (xi − xj )2 k22n−2 − n (k − q) x2n−k−1 xk−1 i j q q=0 i=1,j=1,i6=j k=1 " ) # 2n 2n X X 2n + (2n − k + 1)22n−2 − n (2n − q + 1) x2n−k xk−2 ≥ 0, i j q−k k=n+1 q=k ( n−1 " X k(k + 1) 2n X i=1,j=1,i6=j k=1 2 22n−2 − n k X p=1 p(p + 1) 2n 2 k−p ×xk−1 xk−1 i j 2n−2k−2 X # (xi − xj )4 ≥ 0. p=0 In order to prove (3.4), it is sufficient to show (3.5) vol. 8, iss. 4, art. 102, 2007 Title Page Contents JJ II J I Page 9 of 13 ) x2n−p−4 xpj i Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi n−1 X (n − 1)[(n − 1) + 1] 2n−2 p(p + 1) 2n 2 −n > 0. 2 2 n − p − 1 p=1 Go Back Full Screen Close Considering (2.1), it is sufficient to show n−1 X 2n (n − k) > 22n−2 . k k=0 (3.6) By virtue of as n k = n n−k and P2n k=0 2n k = 22n , inequality (3.6) can be rearranged n−1 X (3.7) 2n X 2n 2n (n − k) (k − n) + > 22n−1 , k k k=0 k=n+1 n−1 2n X X 2n 2n 2n (2n − 2k − 1) + (2k − 2n − 1) > . k k n k=0 k=n+1 2n n−1 2n n+1 2n n n+1 , n Since n ≥ 2 and then inequalities + > is equivalent to 2 > (3.7), (3.6) and (3.5) are valid. The proof of Theorem 1.1 is complete. P Pn Proof of Theorem 1.2. By Lemma 2.2, it is easy to see that 2n i=1 yi = i=1 xi . From Cauchy’s inequality [1, 4], it follows that !2 2n 2n 2 X X yi An ≥ yi , Pi+n−2 y yk|2n k=i i=1 i−1|2n i=1 Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi vol. 8, iss. 4, art. 102, 2007 Title Page Contents JJ II J I Page 10 of 13 Go Back Full Screen Close where An is defined by (2.2) or (2.3) in Lemma 2.2. Therefore, it is sufficient to prove (n − 1) 2n X !2 yi ≥ 2nAn ⇐⇒ n X (n − 1) i=1 !2 ≥ 2n xi i=1 ⇐⇒ (n − 1) n X X xi xj 1≤i<j≤n x2i ≥ 2 i=1 ⇐⇒ X X xi xj 1≤i<j≤2n (xi − xj )2 ≥ 0. 1≤i<j≤2n Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi vol. 8, iss. 4, art. 102, 2007 The proof of Theorem 1.2 is complete. Title Page Proof of Theorem 1.3. Let (3.8) Contents k X 2n 2(n−1) Bn = 2 k(k + 1) − n p(p + 1) . k − p p=1 Then II J I Page 11 of 13 Bn+1 (3.9) JJ k X 2n + 2 2n−2 2 = k(k + 1)2 2 − (n + 1) p(p + 1) k−p p=1 k X 2n 2n + 2 = 4Bn + p(p + 1) 4n − (n + 1) k−p k−p p=1 , 4Bn + k X p=1 p(p + 1)Ck−p Go Back Full Screen Close and Cq − Cq+1 2n + 2 2n + 2 2n 2n − (n + 1) − = 4n − q q+1 q+1 q 2n 2n − q 2n + 2 2n + 2 − q 1− = 4n − (n + 1) 1− q q+1 q q+1 2n + 2 2q − 2n − 1 2n 2q − 2n + 1 = 4n − (n + 1) q q+1 q q+1 2q − 2n + 1 > Cq q+1 for 0 ≤ q ≤ k − 1. Hence, 2n − q Cq > Cq+1 . q+1 Contents From the above inequality and the facts that Cn = 2(2n − 1)(n + 1) 2n n+2 n >0 Bk+2 > 0, Bk+3 > 0, Bk+4 > 0, The proof of inequality (1.3) is complete. ··· , JJ II J I Page 12 of 13 and 2n−q > 0, it follows easily that Cq > 0. Consequently, we have Bn+1 > 4Bn , q+1 and then Bk+2 > 4Bk+1 . As a result, utilization of (3.5) gives Bk+1 > 0, vol. 8, iss. 4, art. 102, 2007 Title Page (3.10) (3.11) Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi Bk+(n−k) = Bn > 0. Go Back Full Screen Close References [1] J.-CH. KUANG, Chángyòng Bùděngshì (Applied Inequalities), 3rd ed., Shāndōng Kēxué Jìshù Chūbǎn Shè (Shandong Science and Technology Press), Jinan City, Shandong Province, China, 2004. (Chinese) [2] J.-P. LI, Question CIQ-103, Communications in Studies of Inequalities, 11(2) (2004), 277. (Chinese) [3] ZH.-P. LIU, X.-G. CHU AND B.-N. GUO, On two algebraic inequalities with even variables, J. Henan Polytech. Univ., 24(5) (2005), 410–414. (Chinese) [4] D. S. MITRINOVIĆ, J. E. PEČARIĆ, AND A. M. FINK, Classical and New Inequalities in Analysis, Kluwer Academic Publishers, 1993. [5] W.-J. ZHANG, Question CIQ-142, Communications in Studies of Inequalities, 12(1) (2005), 93. (Chinese) Algebraic Inequalities with 2n Variables Xiao-Guang Chu, Cheng-En Zhang and Feng Qi vol. 8, iss. 4, art. 102, 2007 Title Page Contents JJ II J I Page 13 of 13 Go Back Full Screen Close